A COMPARATIVE EVALUATION ON SENSE OF COMMUNITY AND STUDENT SATISFACTION IN ONLINE AND OFFLINE ARCHITECTURAL DESIGN STUDIOS - Lukman, Aldyfra Luhulima; Mochtar, Sahid (LANGKAU BETANG: JURNAL ARSITEKTUR, 2024)
Architectural education, which include design studio normally involving physical interaction, in the times of Covid-19 pandemic, needs to be conducted in an online or hybrid format. Online or hybrid format was commonly applied to prevent or minimize the spread of coronavirus. This study intends to identify differences and correlation between sense of community and satisfaction regarding learning process by comparing architecture students participating in offline and online studio. This study measures and compares architecture student performance in offline/ physical design studio and online/ virtual design studio. Sense of community and student satisfaction are operational variables used to measure and compare student performance in this study. Sense of community and satisfaction were chosen because the study focuses on student performance from the students' perspective.  Data were collected through an online questionnaire applying Likert scale to architecture students involved in a hybrid design studio and then analyzed by applying statistical method. The analysis results do not show significant differences on sense of community and satisfaction regarding learning process, between students participating in offline studio and those of online studio. However, this study identifies that sense of community correlates with the satisfaction regarding learning process, in offline and online architectural design studios. The correlation indicates that sense of community and student satisfaction can be used to signify students"™ performance in offline, online or hybrid architectural design studios. This study recommends offline or hybrid mode of learning as the optimum format for architecture design studio in the post-Covid-19 era.